Inter-organizational collaboration and organizational performance: the mediating effect of Big Data Analytics capabilities and the moderating effect of technological dynamism and competitive intensity - Marcelo Werneck Barbosa (2019)
Companies need to implement strategies for collaboration with supply chain partners to make more efficient use of limited resources, manage suppliers’ knowledge, integrate and coordinate production and information flows through the whole supply chain. Collaboration helps organizations gain competitive advantages and improve performance in different ways, such as in terms of financial gains, productivity improvement, reduction of inventory levels and order fulfillment process improvement. It has been possible due to the integration of widespread business information systems, which tend to produce large volumes of information that are beyond the company boundaries to be analyzed. The analysis of such large volumes of data is called in general terms Big Data Analytics (BDA). In order to fully extract benefits from BDA, organizations need to develop analytical capabilities, which may involve managerial, technical and human capabilities, among others. One of the industries that have the potential of extracting most benefits from the adoption of BDA is the retail industry. Retailers are continuously innovating in order to overcome the competition and take advantage of advancing technology. The objective of this research is to understand how collaboration among companies, especially when supported by BDA capabilities, contributes to increasing organizational performance. Besides, we were also interested in analyzing how the dynamic and competitive environment in which retail organizations moderate the impact BDA capabilities might have on organizational performance. In a quantitative study conducted with 323 medium and large-sized Brazilian retail companies, we have found out that interorganizational collaboration has a direct effect on organizational performance as well as that BDA capabilities mediate such relationship. No moderating effect of technological dynamism and competitive intensity was observed. For scholars, this research explores the relationship between collaboration, analytics and organizational performance. Prior research has largely focused on the adoption of analytics in just one company alone, ignoring the influences collaboration might have on such relationships. Besides, the research speciﬁcally examined the mediating role of BDA capabilities in modelling the relationship between inter-organizational collaboration and organizational performance as well as the moderating effect that technological dynamism and competitive intensity may have in such relationship. For practitioners, this study identifies the capabilities that contribute the most to organizational performance when establishing collaboration relationships with supply chain partners. Finally, we expect to stimulate companies to develop collaboration relationships with partners in order to achieve better performance.